ANALISIS PERSPEKTIF GENDER DALAM KEPUASAN KERJA DAN KEINGINAN PINDAH PEKERJAAN (Studi Kasus Pramuniaga di Sinar Supermarket Cabang Bintoro Surabaya) (Lentera, Jurnal Studi Perempuan, 2010)
Abstract Labour’s desire of turnover i s one of several behavior which ccm mctke the frm is not effective and efficient. In the concept. labour s work satisfaction relate w Uh labour s desire ofturnover. Both of them have a negative relationship. Poza s research shown thal there was different between man and women in their desire of turnover. Based on that concept and result of Poza s research, so researcher took this research which used the hypothesis test to know (1) infhtvnce of the labour ’s work satisfaction toward the labour s desire of turnover, in the man labours, (2) influence of the labour ’s work satisfaction toward that the labours desire ofturnover in the woman labours, and (3) based on the result, wich more greater-man or woman labours. This is quantitative research. There are 160 responden t s (there are 130 responden t of man and 30 respondent of woman) This result of research were: (1) in the man respondent t account > t table (3.151 > 2,048) - i t means that there was the signifcant influence at the labour s work satisfcation toward the labour s desire of turnover- there were 72.3% ofthe labour s desire ofturnover were injluenced its work satisfaction, (2) i n the women responden t account > t table ( 3,151 > 2,048) - i t was mean that there were influenced- there were 61.3% ofthe labour ’s desire of turnover were influenced its work satisfaction. and (3) the signifcant influence of the labour s work satisfaction toward the labour s desire ofturnover in the man labours was more greater than the woman labours. This result can use to make dicision in the recruitmen labour. Keywords : labour ’s work satisfaction. labour s desire of turnover